RUMAH TIDAK LAYA HUNI (Studi di Kelurahan Pattingalloang Kecamatan Ujung Tanah Kota Makassar, Indonesian) - Syahban Nur; Andi Agustang; Arlin Adam (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
This research is a mixed study that aims to identify the factors that cause family members to survive in an uninhabitable house. The results of the research data used the direct interview method with a questionnaire to the head of the household regarding information on population, household size, age, gender, ethnicity, religion, employment status, income level, etc. This study uses direct observation, to obtain information about the availability and quality of infrastructure, facilities, and services such as housing conditions, drinking water, supply, roads, drainage systems, and solid waste disposal and management so that data is obtained that two houses do not meet the standard of feasibility. Both in terms of size and design of the house, each house is inhabited by two nuclear families consisting of eight and seven people. Therefore, the subjects of this research are four heads of families who live in RW 5/RT 5 of Pattingalloang Village. The results showed that two factors led to the fact that several nuclear families chose to live in an uninhabitable house in Pattingalloang Village, namely cultural poverty and structural poverty experienced by residents of unfit for habitation.